Optimized recovery of ferulic acid using morpholinium-based ionic liquid: Electrical conduction effects and process efficiency - Nurul Aliaa, Rahman; Wan Mohd Hafizuddin, Wan Yussof; Ahmad Salihin, Samsudin; Mohamad Azmi, Bustam; Roshanida, Abdul Rahman; Alamin, Idris (Springer Science and Business Media Deutschland GmbH, 2025)
Ionic liquids (ILs) are gaining interest for their excellent ionic conductivity, thermal stability, and low environmental impact, making them suitable for various electrochemical applications. Beyond conductivity, ILs show promise in biotechnology, especially for bioseparation and the recovery of valuable compounds. Morpholinium-based ILs, particularly morpholinium tetrafuoroborate ([MOR][BF4]), ofer a green solvent alternative for efciently recovering ferulic acid (FA) from mixed culture fermentation due to their low toxicity and minimal interference with microbial processes. This study focuses on optimizing FA recovery using [MOR][BF4] through central composite design (CCD) and evaluating its conductivity with electrical impedance spectroscopy (EIS). Key parameters of inorganic salt concentration, phase ratio, and recovery time were tested for their efects on recovery efciency. Out of 26 experimental runs, the highest FA recovery of 93.12% was achieved with 0.06 M ammonium chloride, a 1:5 phase ratio, and a 45-min recovery time. Validation experiments confrmed recovery rates between 90.35 and 91.57%, with less than 10% error between predicted and actual results. Additionally, electrochemical analysis showed that [MOR][BF4] has a conductivity of 0.324 mS·cm⁻ 1 at room temperature, making it suitable for electrochemical applications, especially as an electrolyte additive. Overall, the use of [MOR][BF4] in bioseparation has shown a promising advancement due to its high efciency in targeting biomolecules such as FA directly from complex media like fermentation broth without the need for pretreatment.